2018
DOI: 10.3390/buildings8010011
|View full text |Cite
|
Sign up to set email alerts
|

Building Energy Assessment and Computer Simulation Applied to Social Housing in Spain

Abstract: The actual energy consumption and simulated energy performance of a building usually differ. This gap widens in social housing, owing to the characteristics of these buildings and the consumption patterns of economically vulnerable households affected by energy poverty. The aim of this work is to characterise the energy poverty of the households that are representative of those residing in social housing, specifically in blocks of apartments in Southern Europe. The main variables that affect energy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Despite a recent renovation of this residence, energy expenses remained high regarding the renovation program expectations. This result seems to be coherent with the findings of research conducted by (Enertech 2012), (Juan et al 2018) and (Elsharkawy and Rutherford 2015) [3][4][5].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite a recent renovation of this residence, energy expenses remained high regarding the renovation program expectations. This result seems to be coherent with the findings of research conducted by (Enertech 2012), (Juan et al 2018) and (Elsharkawy and Rutherford 2015) [3][4][5].…”
Section: Introductionsupporting
confidence: 91%
“…In addition, this sector suffers from ageing, which results in high energy consumption as well as in high running expenses, degraded quality of life, and high pressure on the budget of low-income occupants. Energy consumption in social housing has been explored in Australia, the Netherlands, the United Kingdom, and Spain [1][2][3][4]. This research confirms the necessity to reduce energy consumption in this sector in order to meet national and regional environmental strategies as well as to improve the quality of life for occupants and to reduce the pressure on the budget of low-income residents.…”
Section: Introductionmentioning
confidence: 52%
“…Reasons for the performance gap are an inadequate assumption of the actual indoor temperature, the influence of user behaviour on actual consumption, and differences between the theoretical calculation and the actual building quality of dwellings. Aranda et al (2018) found that the energy performance gap for social housing is even larger than the energy performance gaps found for other dwellings. Duvier et al (2018) argue that it can be difficult to build and use high-quality datasets.…”
Section: Benchmarking the Energy Performance Of Dwellingsmentioning
confidence: 87%
“…Lamport's bakery algorithm is a computer algorithm suggested by computer expert Leslie Lamport, who wants to improve the convenience of using shared resources in many threads in the context of mutual exclusion [5], [6]. In computer science, it is common for multiple threads to access the same resources simultaneously.…”
Section: Methodsmentioning
confidence: 99%